Sourcing newness: ways of inducing indeterminacy. Issue 5 (3rd September 2017) - Hutter, Michael; Farías, Ignacio
ABSTRACT: This paper engages with the question of the new as the first stage in what may, at a later time, turn into an innovation. Taking our cue from John Dewey, the new is here interpreted as a consequence of indeterminacy. We study practices that induce indeterminacy in order to 'source' the new. Based on findings from a collective research programme, we distinguish three ways of inducing indeterminacy: configuring situations, creating things and risking valuations. For each of these ways of inducing indeterminacy basic variations are described and discussed in greater detail. The three ways of inducing indeterminacy are shown to correspond to a present-centred concept of time that distinguishes the now from a past and a future horizon. The cases presented affirm the claim that the new is not an inevitable consequence of the increasing entanglement of technoscience and the economy but something that needs to be sought for, cared for and actively produced.